Study on impact strength and effect of accelerated weather testing on some properties of polyoxymethylene/silica nanocomposites - Mai, Tran Thi; Trang, Nguyen Thi Thu; Chinh, Nguyen Thuy; Le, Dang Thi Thanh; Hang, Ha Van; Hoang, Thai (Vietnam Journal of Science and Technology, 2020)
The impact strength, some properties and morphology of nanocomposites based on polyoxymethylene (POM) and nanosilica (NS) with different content before and after accelerated weather testing are discussed in this paper. The impact strength of all POM/NS nanocomposite samples are larger than that of POM. Carbonyl index (CI) for nanocomposites are changed after testing responding to the increase of C=O groups content. The results of tensile properties indicate that samples are decomposed by ultraviolet (UV) radiation and photo-oxidation degradation of POM.